7. Total Level of Hemoglobin and Hematocrit Value of Broiler Chickens after Given Moringa Leaves Fermented Flour (Moringa oleifera) in Feed - M. Hasan; Octa Sicillia Rampai; Arman Sayuti; Razali Daud; Abdul Harris; T. Armansyah TR; Gholib Gholib (Universitas Syiah Kuala, 2020)
This study aimed to determine the effect of using Moringa leaves fermented flour in feed stock toward the increasing level of hemoglobin and hematocrit value on broiler chickens. This study used a completely randomized design that consists of 4 treatments and 5 replications. The study group was divided into group P0 which was given with 100% of commercial feed, group P1 was given 95% of commercial feed and Moringa leaves fermented flour 5%, group P2 was given 92.5% of commercial feed and Moringa leaves fermented flour 7.5%, and group P3 was given 90% of commercial feed and Moringa leaves fermented flour 10%. Fermentation using EM4 (Effective Microorganism-4) were able to decrease the crude fiber of Moringa leaves flour. The treatment was conducted for 15 days, then hemoglobin levels and hematocrit values were counted. Data were analyzed using ANOVA completely randomized design with SPSS for Windows 16.0. This research showed that giving Moringa leaves fermented flour for 15 days did not have a significally effect (P0.05). The given Moringa leaves fermented flour in feed for 15 days with 5%, 7.5% and 10% concentration was not show any increase in the levels of hemoglobin and hematocrit values.